The Effect of Risk Propensity, Entrepreneurial Intention and Entrepreneurial Self-Efficacy on Students’ Entrepreneurial Behavior - Atmono, Dwi; Setiawan, Ananda; Rahmattullah, Muhammad (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
The problem of unemployment in Indonesia continues to be a difficult problem to solve. With the increasing unemployment rate, higher education as an educational institution is expected to be able to prepare and equip students to become prospective entrepreneurs by building entrepreneurial character in students through entrepreneurship courses and students who already have their own businesses. This study aims to analyze the effect of risk propensity, entrepreneurial intention, and entrepreneurial self-efficacy on entrepreneurial behavior in college students. The population in this study were students at Lambung Mangkurat University with a total sample of 114 people. The data collection technique used was a questionnaire. The analytical method uses Structural Equation Modeling Partial Least Squares (SEM-PLS). the results of the study show that risk propensity have a positive and significant effect on entrepreneurial intentions. Risk propensity has a positive and significant effect on entrepreneurial self-efficacy. Entrepreneurial intention has a positive and significant effect on entrepreneurial behavior. Entrepreneurial self-efficacy has a positive and significant effect on student entrepreneurial behavior.